Pengembangan Modul Belajar Mandiri Tentang Kepemimpinan Pendidikan Berbasis Competence Based Training Untuk Meningkatkan Kompetensi Kepribadian Guru - Aoetpah, Richard Leonando; Satyawati, Sophia Tri; Wasitohadi (Kelola: Jurnal Manajemen Pendidikan, 2023)
This research aims to describe the leadership of teachers that has been taking place in schools, identify the weaknesses in teachers' educational leadership, and develop a self-learning module on competence-based education leadership to enhance teachers' personal competencies. The research method used a Mixed Method (Sequential) approach with a research and development (R&D) design based on Sugiyono's model integrated with the ADDIE model, consisting of the following five stages: 1) analysis; 2) design; 3) development; 4) implementation; and 5) evaluation. This study was conducted in three public elementary schools in the city of Soe. The research and development period started from July 2022 to May 2023. The research subjects consisted of 15 teachers from three different elementary schools: SD Inpres Oeusapi, SD Inpres Sonapolen, and SD Inpres Tubuhue. The research findings indicate that the educational leadership of teachers in schools is very low, where teachers demonstrate a lack of personality as leaders in the school, lack discipline in terms of time and responsibilities, tend to be individualistic, and have poor communication with fellow teachers. There are weaknesses in educational leadership, as teachers have a lack of knowledge about educational leadership, as evidenced by the absence of books or modules on teacher leadership in the school. Additionally, teachers have insufficient coordination skills with fellow teachers and students, as well as a lack of training on educational leadership in schools. The development of the self-learning module received high validation results from content experts (89.7%), module experts (85.19%), and a questionnaire response from 15 teachers (86.33%).